Physio-Biochemical and Agronomic Responses of Faba Beans to Exogenously Applied Nano-Silicon Under Drought Stress Conditions - Desoky, El-Sayed M.; Mansour, Elsayed; El-Sobky, El-Sayed E. A.; Abdul-Hamid, Mohamed I.; Taha, Taha F.; Elakkad, Hend A.; Arnaout, Safaa M. A. I.; Eid, Rania S. M.; El-Tarabily, Khaled A.; Yasin, Mohamed A. T. (Frontiers in Plant Science, 2021)
Nano-silicon is an efficient novel approach to mitigate the deleterious impacts of drought stress on field crops, which are expected to increase due to climate change, especially in dry regions. This study used a two-season field study to investigate the influence of foliar-applied nano-silicon (0.5, 1, and 1.5 mM) on physiological and biochemical attributes and their impact on crop water productivity (CWP) and agronomic traits of faba bean (Vicia faba). The plants were evaluated under two irrigation regimes; well-watered (100% ETc giving 406 mm ha–1) and drought stress (65% ETc giving 264 mm ha‒1). Drought stress significantly decreased pigment content, gas exchange (leaf net photosynthetic rate, stomatal conductance, and rate of transpiration), water relations (relative water content and membrane stability index), nutrients uptake (N, P, K+ and Ca+2), flavonoids, and phenolic contents. In contrast, it significantly increased oxidative stress (H2O2 and O2•‒) and enzymatic and non-enzymatic antioxidant activities compared to well-watered treatment. All these influences of drought stress were negatively reflected in seed yield-related traits and CWP. However, foliar treatment with nano-silicon, particularly 1.5 mM, limited drought stress and markedly enhanced all the aforementioned parameters. Therefore, exogenously applied nano-silicon could be used to improve CWP, seed, and biological yields under low available water conditions in dry environments.